ASURANSI JIWA ANTARA OBSESI DAN HARAPAN - Suparni, Endang (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Life insurance can protect in case of unforeseen by man. Protection against the risk can be transferred to the insurance company. While our society in the insurance remains low. Given the lifestyle and consumerism still hit, it is a constraint development of the life insurance industry in the country. With increased income, plans to buy an insurance policy are generally not included in the scale of other needs, such as cars, TV-radio, and so on. The need for life insurance has not touched most of the people of Indonesia. The purpose and intent of the study was to determine the wishes and expectations of the people of Indonesia will life insurance services, and determine the level of awareness in Indonesia of the need for insurance. The method uses a descriptive research, and data collection methods derived from observation and literature. The low public awareness and ownership in the life insurance insurance policies in Indonesia far behind Singapore, every citizen has a policy 3-4. Insurance fund in the country, were above other needs. Whereas in our country, the problem is structural. Ability of communities to purchase a life insurance policy is still very weak and life insurance penetration is still far from harapan. Tingkat consumerism is still plagued society , also the lure of a fairly lucrative total prizes of banking products also add to the insurance needs of the community away. For the speculative spirit, put stock in the stock market has its appeal, soaring stock prices, will benefit. As for life insurance, relying only certainty " protection " and guarantee fund future or when undesirable events occur. Apparently the latter is what most people are less interested us, for various reasons above. In addition to the lack of public knowledge in the area of insurance, which indirectly contribute to determine the prospects for life insurance business. Keywords:  Life insurance, obsession and hope.